MENTORING TEACHERS IN THE APPLICATION OF DIGITAL LEARNING MEDIA TO IMPROVE EDUCATION QUALITY - Budianto, Ahmad Andry; Hairit, Artamin (Ngejha, 2024)
This study aims to identify obstacles faced by teachers in implementing digital learning media, develop an effective mentoring program to improve teacher competence, evaluate the impact of mentoring on learning quality, and provide recommendations to stakeholders to support the implementation of digital learning media in a sustainable manner. The research method used is mixed methods with quantitative and qualitative approaches. Data were collected through surveys, in-depth interviews, and observations with teachers from various levels of education. Quantitative data was analysed using descriptive and inferential statistics, while qualitative data was analysed using thematic analysis techniques to dig deeper into teachers' experiences and perceptions. The results showed that the main obstacles faced by teachers include limited access to technology, lack of adequate training, and resistance to change. The mentoring program designed in this study, including intensive training based on the TPACK model and ongoing guidance, proved effective in improving teachers' competence in using digital learning media. An evaluation of the impact of mentoring showed significant improvements in the quality of learning, such as more creative and interactive use of technology, and increased student motivation. This study recommends increasing technology infrastructure support, strengthening ongoing training programs, and collaboration between the government, schools, and education technology providers to ensure the sustainability of digital learning media implementation.